TikTok's Social Media Marketing Gives Strong Impact on Product Sales Increase - Julianti1, Mega; Mudjiarto, Hari; Nagatitha, Partama; Luwiha, Luwiha; Astuti, Widi (Journal of Economic, Religious, and Entrepreneurship (JoERE), 2023)
Marketing is the most essential part of a business. Marketing does not only look at unique products, low and attractive prices, and product availability for consumers. In the current era, one marketing activity is utilizing social media such as TikTok. In 2020 the use of TikTok reached 625 million. In Indonesia, TikTok users reached approximately 30 million users. On the platform, there is a link feature to e-commerce sites on user profiles; therefore, TikTok is a free service with exciting content as a promotional medium in sales. This research aims to find out marketing activities on TikTok media in increasing sales. This study used primary data by distributing questionnaires to online sellers to obtain data from sellers who use the media, with a sample of 35 respondents. The analysis used Simple Regression to test the influence on variables to provide recommendations that TikTok media is very influential in attracting consumers.